ONLINE LEARNING IN SPEAKING CLASS DURINGTHE COVID-19 PANDEMIC - Ahmad Rizal Avisina; Sri Endah Setiarini; Hesthi Herusatoto (Conscientia, 2022)
This research examined the implementation of online learning in an English Speaking class at a school of foreign languages in Indonesia during the Covid-19 pandemic, and it studied the obstacles that the students experienced in the learning process. It was a descriptive qualitative research. Data were obtained from observations, questionnaires, and interviews. The results showed that the implementation of online learning in the Speaking 2 class ran well. The students could follow the instructions given online by the lecturer, and they could apply their knowledge by taking part in class activities, class assignments, and class exams. The lecturer supported the students exactly whenever they needed it. The online learning at the language school, which combined Google Classroom and Zoom Meetings, could make the learning process more optimal. However, the effect of online learning for Speaking class on the students’ outcomes could be not very satisfying.